Influences of crop rotation tillage residue management and winter cover crop on takeall in spring wheat - Cromey, M.G.; Francis, G.S.; Trimmer, L.A.; Tabley, F.J.; Gillespie, R.N.; Fraser, P.M.; Pearson, A.J.; Butler, R.C.; Curtin, D.; Bithell, S.L. (New Zealand Plant Protection, 2008)
The effects of soil and residue management factors (tillage postharvest crop residue management and winter cover crops) and crop rotation (wheat following two barley crops wheat following ryegrass) on take all were compared in a 3year field trial in Canterbury Incidence of takeall was very high in plots that had previously grown barley and very low in plots that followed ryegrass Takeall incidence was also much greater in plots that were disced than in plots that were directdrilled Differences in soil pH and in plant emergence were also recorded between disced and directdrilled plots but there was no evidence that they caused the increased levels of takeall There was a tendency towards reduced yields in the disced plots that had severe levels of takeall